2016
DOI: 10.1186/s13023-016-0447-6
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation into cognition and disease progression in spinocerebellar ataxia types 1, 2, 3, 6, and 7

Abstract: BackgroundThe natural history of clinical symptoms in the spinocerebellar ataxias (SCA)s has been well characterised. However there is little longitudinal data comparing cognitive changes in the most common SCA subtypes over time. The present study provides a preliminary longitudinal characterisation of the clinical and cognitive profiles in patients with SCA1, SCA2, SCA3, SCA6 and SCA7, with the aim of elucidating the role of the cerebellum in cognition.Methods13 patients with different SCAs all caused by CAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 47 publications
12
74
0
Order By: Relevance
“…Later investigations replicated the existence of cognitive improvement after cerebellar injury [124]. Studies examining the natural history of genetic cerebellar disorders indicate that cognitive deficits as measured by neuropsychological testing may be absent or minor in the early stages of cerebellar degeneration [125].…”
Section: Cerebellar Cognitive Reserve (Guell X Schmahmann Jd)mentioning
confidence: 91%
“…Later investigations replicated the existence of cognitive improvement after cerebellar injury [124]. Studies examining the natural history of genetic cerebellar disorders indicate that cognitive deficits as measured by neuropsychological testing may be absent or minor in the early stages of cerebellar degeneration [125].…”
Section: Cerebellar Cognitive Reserve (Guell X Schmahmann Jd)mentioning
confidence: 91%
“…This dissociation could reflect distinct pathophysiology in SCA subtypes. ToM deterioration was found with SCA progression (Moriarty et al, 2016). Deficient representation of mental states was also seen in six patients with superficial siderosis, a condition with diffuse hemosiderin depots in superficial layers throughout the brain, but mainly affecting the brainstem and cerebellum (van Harskamp et al, 2005).…”
Section: Evidence From Cerebellar Degenerationmentioning
confidence: 96%
“…Concerning SCA6, earlier studies reported intact cognition on the basis of clinical examination and anamnesis [39][40][41]. Eight studies examined cognitive functions in SCA6 by means of neuropsychological test batteries [42][43][44][45][46][47][48][49]. The most frequent finding was a mild deficit in executive functions, whilst intelligence, memory and attention were largely spared.…”
Section: Review Of the Literaturementioning
confidence: 99%